Using model texts as a form of feedback in L2 writing. (April 2020) - Kang, Eun Young
Abstract: Recently, researchers have proposed that model texts can be used as an effective feedback technique. To contribute to the ongoing research, the study examined the extent to which models can result in the improvement of L2 writers' subsequent drafts using a three-stage writing task: (i) writing (pretest), (ii) comparing (treatment), and (iii) rewriting (posttest). Forty Grade 11 EFL students wrote an argumentative essay and then were assigned to either an experimental ( n = 20) or a control group ( n = 20). The experimental group received two model texts to compare their writing against, whereas the control group ( n = 20) was asked to self-correct their initial composition. The results suggested that learners mainly noticed their lexical problems at the initial stage of writing, which drew their attention to the words included in the models. They subsequently incorporated some of the words into their rewriting. By incorporating linguistic elements from the model texts, the participants in the experimental group in general received higher writing scores on the posttest compared to those in the self-correction group. Model texts were found to be particularly effective in improving vocabulary and content of L2 learners' writing.